2016
DOI: 10.1017/s095026881600234x
|View full text |Cite
|
Sign up to set email alerts
|

Differences inNeisseria gonorrhoeaepopulation structure and antimicrobial resistance pattern between men who have sex with men and heterosexuals

Abstract: This study compared the antimicrobial susceptibility and genotypes of strains of Neisseria gonorrhoeae isolated from men who have sex with men (MSM) and from heterosexuals. One hundred and eleven strains were characterized from 107 patients, comprising 57 strains from 54 heterosexuals and 54 strains from 53 MSM. Antimicrobial resistance rates were higher in strains from heterosexual patients, with resistance to cefixime (P = 0·0159) and ciprofloxacin (P = 0·002) being significantly higher. Typing by N. gonorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
1
9
2
1
Order By: Relevance
“…Most (74%) fell in to 24 different STs, which were clustered in 10 genogroups, with G2400 and G2992 being the most predominant. Contrary to our results, a statistically significant relationship between the latter genogroups and MSM has been previously reported [20, 22]. Although three-quarters of our isolates were recovered from MSM, we found a statistically significant relationship between G2400 and heterosexual patients, while G2992 seemed arbitrarily distributed between MSM and heterosexual subjects.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Most (74%) fell in to 24 different STs, which were clustered in 10 genogroups, with G2400 and G2992 being the most predominant. Contrary to our results, a statistically significant relationship between the latter genogroups and MSM has been previously reported [20, 22]. Although three-quarters of our isolates were recovered from MSM, we found a statistically significant relationship between G2400 and heterosexual patients, while G2992 seemed arbitrarily distributed between MSM and heterosexual subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…Although three-quarters of our isolates were recovered from MSM, we found a statistically significant relationship between G2400 and heterosexual patients, while G2992 seemed arbitrarily distributed between MSM and heterosexual subjects. It is also noteworthy that G1407, the most prevalent genogroup seen in the previous studies [20, 22, 24], was one of the less prevalent genogroups found here and represented only by three strains. G1407, which is widely disseminated, has been associated with cefixime and ceftriaxone resistance [3, 20, 36], and specifically with cephalosporin treatment failures internationally [3].…”
Section: Discussionsupporting
confidence: 59%
“…While the pattern is not universal, gonococcal isolates from MSM often demonstrate greater prevalence of antimicrobial resistance than isolates from heterosexuals. [58][59][60][61] Although new resistant strains are often initially detected in heterosexuals, such strains can disseminate rapidly in sexual networks of MSM. [62][63][64] The spread of resistant strains among MSM may be facilitated by the partnership and network phenomena outlined above.…”
Section: Gay Bisexual and Other Men Who Have Sex With Menmentioning
confidence: 99%
“…Over one third of studies used isolates collected in the UK (37%; 18/49), 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 from consecutive patients during the study time period (35%; 17/49), 11 , 14 , 15 , 16 , 17 , 21 , 22 , 24 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 or limited inclusion of isolates to those known to be resistant to a specific antimicrobial (35%; 17/49). 9 , 10 , 13 , 18 , 19 , 20 , 23 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 The number of isolates sampled ranged from six to 3326, with studies covering a time period of less than six months to nine years (Supplementary material).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used NG-MAST (82%; 40/49), 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 two used MLST (4%; 2/49), 34 , 54 and seven used WGS (14%; 7/49), 23 , 24 , 25 , 45 , 55 , 56 , 57 ( Fig. 2 ).…”
Section: Resultsunclassified